The Right of Abode Issue: Its Implication on Translation - Poon Wai-Yee, Emily (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThis paper explores the limitations on legal translation strategy by looking at the right of abode issue in Hong Kong—the very first case in which the role of interpretation was argued since the return of sovereignty to China in 1997. The different approaches to interpreting the mini-constitution, the Basic Law, by the Court of Final Appeal, the Hong Kong Government and the Central Authorities as well as public opinion on the issue will leave translators with no choice but to translate a text that carries terms with open interpretation as literally as possible so as not to affect the substance of the original text. This paper also discusses the strategy of translating a judgement made by a legal body. Legal bilingualism should enable the general public to understand the law to a greater extent than they previously did. A user-friendly approach to translation will accelerate the assimilation of the common law into the Chinese culture and language.